UN reforms for the 2030 agenda: Are the HLPF's working methods and practices "fit for purpose"? - Marianne Beisheim (Stiftung Wissenschaft und Politik (SWP), 2018)
UN Secretary-General António Guterres has initiated various reform processes to effectively implement the 2030 Agenda for Sustainable Development. Member states have already agreed to reorganise the United Nations (UN) development system. While further in-depth reforms are necessary, they would be difficult to realise in the current political context. Improvements to working methods and practices, however, are within the realm of the possible. This study starts by examining what working methods and practices helped member states consensually adopt the ambitious 2030 Agenda, including the Sustainable Development Goals (SDGs) agreed in it, in September 2015. The High-Level Political Forum on Sustainable Development (HLPF) is currently the heart of the UN's sustainable development governance. It is meant to support member states in taking on political leadership and responsibility for implementing the 2030 Agenda and SDGs. An analysis will show, however, that the HLPF risks failing in its task: the complexity of the 2030 Agenda, the HLPF's broad mandate, the large number of participants, and their high expectations are creating problems for a forum that - having been founded in 2013 - is not sufficiently equipped for this. In 2016 member states already decided to review the format and organisational aspects of the HLPF in 2019-2020. Drawing on an analysis of the HLPF's current working methods and practices, this study explores ideas for improvements.
Keywords: 320